Mixed-Media Collage An Exploration of Contemporary Artists, Methods, and Materials - Holly Harrison (USA Quarry Books, 2007)
More than 60 new mixed-media collages by leading mixed-media artists. Mixed-media collage artists are embracing, unearthing, and reconstructing the flotsam and jetsam of modern life with abandon, integrating discards along with a range of art materials and novel techniques to create compelling, new works. Original, idiosyncratic, and delightful, this catch-as-catch-can approach to making art is inspiring and can have eye-catching results. It can also have its own set of technical challenges. Mixed-Media Collage takes you into the studios of five talented mixed-media artists: Laurinda Bedingfield, Barbara De Pirro, Paula Grasdal, Sharon McCartney, and Teesha Moore. The artists reveal their own step-by-step processes, offer tips on working with unconventional materials, and share their insights on creativity and finding inspiration. A deluxe gallery features forty never-before published mixed-media pieces, complete with detailed descriptions of the work and the materials used to create them.
Keywords: Art; Nonfiction